STEM inquiry and its practice in K-12 classrooms : activities, characteristics and enactment - Tan, Aik-Ling; Teo, Tang Wee; Chang, Jina; Choy, Ban Heng (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Through examining the theoretical ideas of disciplinarity and disciplinary practices, the book presents instructional aspects for teachers to explore when engaged with integrated STEM inquiry. Are you interested to understand the difference between science inquiry and STEM inquiry? Do you want to introduce integrated STEM problem-solving to your students but need help with the key features of STEM inquiry? This book presents in-depth discussions related to the features and affordances of integrated STEM inquiry. Written for K-12 teachers and training teachers, this book conceptualizes STEM inquiry and integrated STEM and their enactment, using three practical STEM instructional frameworks: problem-centric, solution/design-centric, and user-centric STEM. The three STEM instructional frameworks serve as a key anchor for teachers to interpret and apply in planning various STEM lessons in meaningful, practical, and coherent ways. Whether you are an aspiring K-12 STEM teacher or an in-service teacher teaching K-12 students, the ideas of integrated STEM inquiry presented in this book challenge educators to think about the principles of integrated STEM inquiry and how it can be incorporated into classroom practice and lessons"--
Keywords: Science -- Study and teaching (Primary); Technology -- Study and teaching (Primary); Engineering -- Study and teaching (Primary); Mathematics -- Study and teaching (Primary); Science -- Study and teaching (Secondary); Technology -- Study and teaching (Secondary); Engineering -- Study and teaching (Secondary); Mathematics -- Study and teaching (Secondary); EDUCATION / Teaching Methods & Materials / Science & Technology